Reproductive biology of the parrotfi sh, Sparisoma frondosum (Actinopterygii: Scaridae), caught off central Pernambuco State - Véras, Dráusio Pinheiro; Hazin, Fábio Hissa Vieira; Costa e Silva, Regina Coeli de O.; Moura, Lays da Rocha; Tolotti, Mariana Travassos (Arquivos de Ciências do Mar, 2009)
The present work aimed at studying the reproductive biology of parrotfi sh Sparisoma frondosum caught in Pernambuco State continental Shelf. From March, 2005 to January, 2008, 185 specimens, with standard length (SL) ranging from 12.6 to 29.5 cm were analyzed. The sexual proportion between male and female was 1:1.2. The monthly mean Gonad Index (G.I.) for females was higher in February, while for males the highest value was observed in April. The size at the fi rst sexual maturity (L50) for females was estimated at 17.0 cm SL and for males at 17.7 cm SL. The average fecundity was estimated as 80,276 oocytes. These results indicate that the species presents multiple or batch spawning, with reproduction occurring all year round.